Sovereign Credit Rating Mismatches - António Afonso; André Albuquerque (Notas Económicas, 2018)
We study the factors behind ratings mismatches in sovereign credit ratings from different agencies, for the period 1980‑‑2015. Using random effects ordered and simple probit approaches, we find that structural balances and the existence of a default in the last ten years were the least significant variables. In addition, the level of net debt, budget balances, GDP per capita and the existence of a default in the last five years were found to be the most relevant variables for rating mismatches across agencies. For speculative‑‑grade ratings, a default in the last two or five years decreases the rating difference between S&P and Fitch. For the positive rating difference between S&P and Moody’s, and for investment‑‑grade ratings, an increase in external debt leads to a smaller rating gap between the two agencies.